2015
DOI: 10.1007/s11764-014-0421-z
|View full text |Cite
|
Sign up to set email alerts
|

Group medical consultations in the follow-up of breast cancer: a randomized feasibility study

Abstract: BCS may benefit from GMCs by receiving more information and additional peer support. GMCs cover all aspects of follow-up and may be a good alternative for individual follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 52 publications
1
10
0
Order By: Relevance
“…Needs for social support are being addressed by GMCs and were positively evaluated by carriers as well. These findings are in line with results from a study on GMCs during follow-up of breast cancer [18].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Needs for social support are being addressed by GMCs and were positively evaluated by carriers as well. These findings are in line with results from a study on GMCs during follow-up of breast cancer [18].…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies revealed beneficial effects of GMCs on patient and professional satisfaction, information provision, health behavior, self-efficacy and knowledge of the disease, quality of life, and quality of care [14][15][16]. Recently, the interest in GMCs in cancer follow-up care is also growing [17,18].…”
mentioning
confidence: 99%
“…One trial reported on healthcare provider satisfaction with the SMA for breast cancer survivors, measured using a 5-point scale. 24 Healthcare provider satisfaction was no different between SMA and usual care. 24…”
Section: Resultsmentioning
confidence: 92%
“…22 Of the four studies that measured patient satisfaction, there was no significant difference between SMA and usual care. 21,23,24,25…”
Section: Resultsmentioning
confidence: 99%
“…Feasibility was analyzed using several areas of focus, as suggested by Bowen et al (2009) [78,79]. Participant characteristics and Google analytics were used to assess expressed interest.…”
Section: Methodsmentioning
confidence: 99%